2012
DOI: 10.1002/em.21680
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of styrene–acrylonitrile trimer in brain, liver, and blood cells of weanling F344 rats

Abstract: Styrene–acrylonitrile Trimer (SAN Trimer), a by-product in production of acrylonitrile styrene plastics, was identified at a Superfund site in Dover Township, NJ, where childhood cancer incidence rates were elevated for a period of several years. SAN Trimer was therefore tested by the National Toxicology Program in a 2-year perinatal carcinogenicity study in F344/N rats and a bacterial mutagenicity assay; both studies gave negative results. To further characterize its genotoxicity, SAN Trimer was subsequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Interestingly, a stand-alone genetic toxicology study was conducted by the NTP with the same batch of SAN Trimer as used in the current bioassay confirmed the lack of mutagenicity seen in the earlier bacterial and human studies, but found that SAN Trimer, administered once daily for 4 days by gavage to male and female F344/N juvenile rats was associated with significantly increased levels of DNA damage in brain cells from the cerebrum and cerebellum, measured by the Comet assay, and chromosomal damage in peripheral blood reticulocytes, measured by the micronucleus assay (NTP 2012, Hobb et al, 2012). Additional evidence of DNA damage, measured by the Comet assay, was seen in liver cells and peripheral blood leukocytes of exposed male and female rats.…”
Section: Discussionsupporting
confidence: 77%
“…Interestingly, a stand-alone genetic toxicology study was conducted by the NTP with the same batch of SAN Trimer as used in the current bioassay confirmed the lack of mutagenicity seen in the earlier bacterial and human studies, but found that SAN Trimer, administered once daily for 4 days by gavage to male and female F344/N juvenile rats was associated with significantly increased levels of DNA damage in brain cells from the cerebrum and cerebellum, measured by the Comet assay, and chromosomal damage in peripheral blood reticulocytes, measured by the micronucleus assay (NTP 2012, Hobb et al, 2012). Additional evidence of DNA damage, measured by the Comet assay, was seen in liver cells and peripheral blood leukocytes of exposed male and female rats.…”
Section: Discussionsupporting
confidence: 77%
“…Slides were prepared and analyzed as described previously (Hobbs et al ; Recio et al ) with some modifications. In a laboratory with controlled humidity (≤60%), samples were thawed on ice and a portion of the cell suspension was diluted with 0.5% low melting point agarose (Lonza, Walkersville, MD) dissolved in Dulbecco's phosphate buffer (Ca +2 , Mg +2 , and phenol free) at 37°C and layered onto each well of a 2‐well CometSlide™ (Trevigen, Gaithersburg, MD).…”
Section: Methodsmentioning
confidence: 99%
“…As an example, the method description for Comet and MN assay data analysis is used from a recently published study on the genotoxicity of Styrene Acrylonitrile Trimer in brain, liver, and blood cells of weanling F344 rats 45 : The Shapiro-Wilk test … was used to assess normality of the vehicle control group. Data that were normally distributed were analyzed using an independent sample's t-test to compare each dose level to the concurrent control … normally distributed data were also tested for homogeneity of variances using the F test; for data of unequal variances, the Welch's approximation … was used.…”
Section: Decision Tree Approachesmentioning
confidence: 99%